Políticas educacionais de atenção aos estudantes com deficiências e necessidades educacionais específicas: um estudo a partir de um instituto federal de educação, ciência e tecnologia do Rio Grande do Sul - Maria, Paula Mrus (2020)
The study presented has as its central theme the policies to assist students with disabilities and specific educational needs and was developed with the purpose of understanding their conformations, from the context of the Federal Institute of Education, Science and Technology of Rio Grande do Sul - IFRS and its Restinga Campus. The attention to students, from the perspective of social policy, is a recent construction and has acted together with the inequalities that are established in the daily life of educational institutions. Their compensatory and individualized character needs to be understood together with the selective and unequal school relations, as well as with the excluding sociability of the capitalist mode of production. In this sense, this study is guided by the critical dialectical method that makes it possible to understand the historical and material bases that sustain the unequal educational development of students with disabilities and specific educational needs, as well as the conflicting relationship between the school and human differences in their multiple dimensions. The research developed is characterized as empirical, exploratory, and qualitative approach. Data were collected from the documental analysis of the policies of attention to students of the IFRS, participant observation in eleven visits to the Restinga Campus and interviews with fourteen subjects. The interviewees were seven students with disabilities and/or specific educational needs and seven federal employees, from these three professors and four technical-administrative staffs who work directly with the structuring of these policies on the mentioned Campus. The Content Analysis technique was used to analyze the data. The results obtained made it possible to understand how the inclusive process is established in everyday school life and express that attention to students, from an Inclusive Education perspective, is still a challenge to be achieved. The school still does not recognize differences and diversity as an inherent part of this dynamic, which reinforces educational inequalities. The attention to students has been implemented through different policies and institutional devices, revealing that the mediation of the processes of exclusion is carried out through fragmented actions. In that way, these policies have developed in a disjointed way of the teaching processes and teaching practice, centralizing the fragilities of educational inclusion as a matter of individual student order. Thus, these policies, despite constituting resistance to educational inequalities, have also acted as a mechanism to justify low investment and institutional omission in the face of situations of failure and school exclusion. The supply of services and resources to students has been far from the right to learning and the construction of knowledge produced by the school, as well as respect for the diversity established in school relations. For this to occur, it is necessary to develop institutional management processes built collectively between the rectory and its campuses that incorporate educational inclusion and attention to inequalities as a priority guideline to be attended to, especially in the classroom space, where the main weaknesses of the inclusive process are found.